Development of Android-Based Digital Books on the Diversity of Indonesian Society Integrating Science Concepts: A Bhinneka Tunggal Ika Framework - Hendra Taufik; Suryanef; Al Rafni; Nofrion (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to develop Android-based digital books on the diversity of Indonesian society, integrating science concepts within the Bhinneka Tunggal Ika framework. Using the Four-D R&D model—Define, Design, Develop, and Disseminate—the research produced a digital teaching material for Pancasila and Citizenship Education tailored to ninth-grade students. The content was validated by experts and tested in limited trials, showing that it meets educational standards and effectively supports student understanding of cultural diversity. The digital book integrates text, images, videos, and animations to create an engaging and interactive learning experience. It is designed to be accessible both in class and at home, promoting self-directed learning while fostering appreciation for Indonesia’s multicultural identity. The findings show that this media enhances students’ enthusiasm, motivation, and comprehension of diversity in the context of national unity. By combining technology with civic education, the digital book serves as an innovative tool to strengthen character values and promote harmony among diverse communities. This development contributes to modernizing teaching methods and making more relevant and impactful for today’s digital-native generation.